Preparation of carbon aerogel supported platinum catalysts for the selective hydrogenation of cinnamaldehyde - Bruno F. Machado (2012)
The selective hydrogenation of cinnamaldehyde is investigated using platinum catalysts supported on carbon aerogels with different textural and chemical properties. Despite the large amount of oxygenated surface groups introduced after the oxidation step, the original porosity of the carbon aerogels is maintained. The oxidation treatments performed on the materials are found to strongly influence the surface chemistry which in turn affects the Pt dispersion, yielding larger metal particles after the chemical modifications and the H-2 pre-treatment. The presence of mesopores and the increase of the acidic character in the carbon aerogels lead to a higher catalytic activity and selectivity towards cinnamyl alcohol when compared with that obtained for the untreated materials. A thermal treatment at 973 K is found to favor the hydrogenation of the olefinic bond when using carbon aerogels, due to the remaining oxygenated surface groups, at variance with other previously reported carbon supports (xerogels and nanotubes).